Three new Praociini (Coleoptera: Tenebrionidae) from Peninsula Valdés (Argentina), with zoogeographical and ecological remarks - Flores, Gustavo E.; Carrara, Rodolfo; Cheli, Germán H. (Zootaxa, 2011)
Three new taxa from Peninsula Valdés (Argentina) are described for the tribe Praociini (Pimeliinae): Calymmophorus peninsularis sp. nov. and two subspecies of Praocis (Hemipraocis) sellata Berg 1889: P. (H.) sellata peninsularis ssp. nov. and P. (H.) sellata granulipennis ssp. nov. The first two taxa are endemic to the peninsula and the third one is distributed in and outside the peninsula. Distribution maps, habitat records and habitus photographs for these three new taxa are included, with comparisons to other known species of the genera. An identification key to the five subspecies of Praocis (Hemipraocis) sellata is provided. A discussion is presented on endemicity and sympatry of two species of Calymmophorus Solier 1840, and non-sympatry of two subspecies of Praocis (Hemipraocis) sellata. The following synonymy is reported and illustrated: Praocis sellata bruchi Kulzer 1958 = Praocis sellata topali Kaszab 1964 syn. nov.